The impact of a school meal program on student’s cognitive development: Evidence from Ecuador - Gaibor, Pablo (2023)
This paper evaluates, for the first time, the impact of the School Meal Program (PAE) on the scores of the Ser Bachiller test for the period 2015-2019, in Ecuador. For this, a difference-in-differences (DiD) method is used in combination with propensity score matching (PSM). First, matching with student-level information is used to compare individuals who receive the treatment with those who do not. This is done by means of the nearest neighbor criterion and inverse probability weighting. Finally, the average grades are calculated at the level of Educational Units, and DiD procedure is performed at the level of Educational Units in the study period, obtaining evidence that there is a positive impact of the PAE on the grades of beneficiary students.